2023
DOI: 10.2196/45868
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Impact of Digital Health Maturity on Patient Experience, Population Health, Health Care Costs, and Provider Experience: Mixed Methods Case Study

Leanna Woods,
Ronald Dendere,
Rebekah Eden
et al.

Abstract: Background Health care organizations understand the importance of new technology implementations; however, the best strategy for implementing successful digital transformations is often unclear. Digital health maturity assessments allow providers to understand the progress made toward technology-enhanced health service delivery. Existing models have been criticized for their lack of depth and breadth because of their technology focus and neglect of meaningful outcomes. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Given the broad recognition of the increasing need to address SEDoH in healthcare, the SIMM is a timely and important tool to help identify areas where organizations are not operating optimally and allow them to determine strategies that can improve their operations and processes. Further, the impact of maturity model implementation can be learned from a recent mixed methods case study in Australia that indicated that higher digital health maturity was associated with better outcomes, including maintaining a patient health record, tracking patient experience data, tracking the patient journey, and mitigating the clinical risk [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the broad recognition of the increasing need to address SEDoH in healthcare, the SIMM is a timely and important tool to help identify areas where organizations are not operating optimally and allow them to determine strategies that can improve their operations and processes. Further, the impact of maturity model implementation can be learned from a recent mixed methods case study in Australia that indicated that higher digital health maturity was associated with better outcomes, including maintaining a patient health record, tracking patient experience data, tracking the patient journey, and mitigating the clinical risk [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another goal of digital health is improving the experience of each patient, as well as the experience of the doctor and other non-medical providers. The final objective is to address health disparities and improve them with an individualized view of each patient [ 234 , 235 ].…”
Section: Digital Health and Wearable Technologiesmentioning
confidence: 99%